Functional Films of Polymer-Nanocomposites by Electrospinning for Advanced Electronics, Clean Energy Conversion, and Storage - M. M., Yusoff; Rajan, Jose; Archana, Panikar Sathyaseelan; Viet, Anh Le; Bao, Qiao Liang; Loh, Kian Ping; Anil Kumar, Gopinathan Nair M.; Ramakrishna, Seeram (Trans Tech Publications, Switzerland, 2012)
An approach for making functional films of polymer – nanocomposites under the framework of nanotechnology is presented. In this methodology, nanowires of an inorganic functional material are dispersed in a functional polymeric medium and the resultant solution is developed into solid films by electrospinning technique. The final structure is a nanofibrous film – each nanofiber contains a percolating network of inorganic nanowires. The nanowires reduce the percolation threshold compared to those nanoparticles and maintain the flexibility and/or light weight of the polymers and nanomaterials. This methodology has been tested for a number of material architectures for electronic and energy devices.